PROPOSING LOCALIZATION QUALITY ASSESSMENT FOR TELEVISION SERIES AND PRINTED COMICS SERIES IN REGARD TO THE LOCALIZATION ELEMENT SIMILARITIES - Wulandari - Wulandari (CrossOver, 2021)
AbstractLocalization quality assessment (LQA) is required to reveal the quality of particular localized products but the diversity of LQA types is a problem that needs to be tackled. This research attempts to describe the localization element similarities in audiovisual and non-audiovisual localization assessment and its contribute to the design of localization quality assessment designed for both localized products. This research applies descriptive qualitative as the research design. This paper uses the source data from American educational children’s namely Sesame Street which realesed in 1969 and its Indonesian localization version Jalan Sesama which realesed in 2007. For the non-audiovisual product, it takes American comic series The Amazing Spiderman by Marvel that published in 1963 and its Indonesian localization version Labah-labah Merah by Kus Bramiana that published in 1978. In striving to answer to the problem statement, this research uses the theory of LQA by Esselink (2000) and Zanettin (2015) for both the localization of television series and comics to analyze the data. The findings analyze the similarities which revolve around linguistics, operational, and cosmetics elements of the localized products.